Crossover from charge order to strain glass in phase separated manganite thin films: Impact of thermal cycling and substrate induced strain. (January 2015) - Agarwal, Vasudha; Sharma, Geetanjali; Siwach, P.K.; Maurya, K.K.; Awana, V.P.S.; Singh, H.K.
Abstract: The magnetic and electrical transport properties of single crystalline La1− x − y Pr y Ca x MnO3 ( x ≈0.42, y ≈0.40) thin films ( 140 nm) deposited on (1 1 0) oriented LaAlO3 and SrTiO3 substrates have been investigated. The magnetotransport properties of these films exhibit substrate dependent phase separation and a crossover from the high temperature antiferromagnetic-charge ordered insulator (AFM-COI) phase ( T > T C ) to strain glass ( T < T g ). At intermediate temperatures ( T g ≤ T ≤ T C ) dynamical liquid having prominent thermal-magneto-resistive hysteresis dominates in the cooling cycle while in the warming cycle it is preceded by ferromagnetic metal (FMM) phase. Magnetic fields required to drive AFM-COI to FMM phase transition are higher than required for the strain glass to FMM transformation. The magneto-electric transitions and temperature span of the distinct magnetic regimes are sensitive to the thermal cycling and substrate induced strain. Highlights: Phase separated manganite films. AFM-FMM transition. Frustration induced magnetic liquid. COI-FMM Crossover.